The Coupling Coordinated Relationship Between New-type Urbanization, Eco-Environment and its Driving Mechanism: A Case of Guanzhong, China - Dong, Liyuan; Shang, Juan; Ali, Rizwan; Rehman, Ramiz U (Frontiers in Environmental Science, 2021)
As an important platform for participating in international competition and cooperation, supporting economic growth and promoting coordinated regional development, urban agglomeration plays an important role in China’s economic, social and urbanization development. At this time, the Guanzhong Plain urban agglomeration (GZPUA), as the second largest urban agglomeration in western China, has a moderate population density. The high demand and high input of resources for population growth make the regional ecological destruction and environmental pollution more prominent. Therefore, it is of great practical significance to study the coordinated development of urbanization and ecological environment in GZPUA. By using the panel data of the GZPUA of China between 2008 and 2017, this study constructed evaluation index system of new-type urbanization and ecological environment quality and calculated the weights of the indices within the evaluation system via the improved entropy weight method, finally determined the new-type urbanization and ecological environment quality of each city. Then the coupling coordination degree model was used to analyze the coupling coordination relationship between two systems of GZPUA and their coupling stages and levels. In addition, the driving mechanism of their coordination degree was explored by using geographic detector method. The results show that: (1) The GZPUA new-type urbanization quality is characterized by both slow growth except Xi’an by a rapid increase. The ecological environment quality is characterized by both slow growth and fluctuations, except Qingyang by a decrease. (2) The overall level of coupling and coordinated development of new-type urbanization and ecological environment in GZPUA is low, but it is on the rise. (3) There were significant spatial differences in the coupling coordination degree, and the regions with high coordination degree distributed in a “one point” pattern (Xi’an) in 2017. The 11 cities can be divided into high-high type, high-low type, low-low type and low-high type, different types should take different development paths. (4) The coordinated development of new-type urbanization and ecological environment is a process in which various driving factors act on different driving forces. These driving forces can be summarized as market driving force, endogenous driving force, outward driving force and administrative driving force.